Evaluation of the Clean Water Supply System Development Program in Bojonegoro from the SDGs Perspective - Febriani, Tiara Ayu Surya; Huda, Muhammad Miftahul; Junadi, Junadi (Jurnal Demokrasi dan Politik Lokal, 2025)
This study aims to evaluate the clean water supply system development program in Bojonegoro Regency in encouraging the achievement of Sustainable Development Goals (SDGs) point 6, which is oriented towards universal access to clean water. The study used a qualitative descriptive method, with primary data from interviews and field observations and secondary data from related documents. The results showed that this program increased access to clean water by 98.23%, approaching the RPJMD target and positively impacting the community. Evaluation based on William N. Dunn's theory showed high effectiveness and efficiency, with optimal budget management. However, challenges in equal access, adequacy, and accuracy of targets still need to be improved. The inequality of development distribution was seen in several sub-districts affected by drought. However, this program received a positive response from the community because it improved the quality of life and reduced health risks. Further efforts are needed to ensure the equality and sustainability of the program to achieve the SDGs targets by 2030.